Application of novel multiple-dimensional cobalt oxides as the electroactive material on supercapacitors. Issue 76 (1st August 2016) - Hong, Wei-Lung; Lin, Lu-Yin; Liu, Yu-Bin; Lin, Lu-Ying; Tu, Chao-Chi
Abstract : A two-step hydrothermal reaction is used to synthesize the cobalt oxide nanomaterial composed of the one, two, and three dimensional nanostructures on the nickel foam. Abstract : Cobalt oxide is one of the attractive materials for supercapacitors (SCs) applying a faradaic reaction to store electrons. Researchers are devoted to synthesizing novel structures of cobalt oxides with different dimensions and designing layer-by-layer configurations composed of different morphologies to pursue multiple functions for attaining a better performance of the SC electrode. In this study, a two-step hydrothermal reaction is used to synthesize a cobalt oxide nanostructure composed of one, two, and three dimensional nanostructures on nickel foam. Superior to the traditional layer-by-layer configuration, this method is advantageous because it simultaneously synthesizes nanomaterials with multiple dimensions on the substrate, instead of combining the nanomaterials with different dimensions after each material has been synthesized separately. A one-dimensional (1D) cobalt oxide nanostem underlayer possesses speedy straight pathways for charge transfer, and three-dimensional (3D) nanoflowers composed of two-dimensional (2D) nanopetals distributed uniformly on top of the nanostem array provide a large active surface area for faradaic reactions. A high specific capacitance ( C F ) value of 916.9 F g −1 is obtained for the corresponding SC electrode using the cyclic voltammetry (CV) technique at a scan rate of 20 mV s −1 . The results provide a new concept to in situ combine nanomaterials with multiple dimensions at once, avoiding time-consuming issues and adherence problems at the interface between different structures.